Alterações cardiovasculares induzidas pela peçonha da serpente Bothrops leucurus - Naumann, Gustavo Baptista (2018)
Bothrops leucurus (white tail jararaca) is the main responsible for ophidian accidents in the northeastern region of Brazil and northern Espírito Santo. Several studies have evaluated the biochemical features of this snake’s venom, as well as its local effects. However, systemic effects – in particular cardiovascular effects – remain rather poorly explored. In the present study, we sought to investigate the acute cardiovascular activities induced by B. leucurus venom (VB) in vivo and in vitro. In anaesthetized rats it was demonstrated that BlV (10-100µg/kg) induces immediate and transient hypotension, while maximum response was observed in 5 min and a return to baseline was observed in ≈ 20 minutes. No change in the heart rate of the animals was observed. In vitro effects were evaluated on pre-contracted mesenteric artery rings with phenylephrine, employing a resistance myograph.